Drift effects and up–down asymmetry in balanced double‐null DIII‐D divertor configurations. Issue 6 (26th June 2018) - Meier, E.T.; Covele, B.; Guo, H.Y.; Thomas, D.M.
Abstract : In a preliminary design study for a small‐angle slot (SAS) divertor configuration suitable for DIII‐D double‐null advanced tokamak (AT) plasmas, a conceptual "SAS 2" slot divertor configuration has been modelled with SOLPS‐ITER. A balanced double‐null equilibrium, representing an H‐mode AT plasma, is employed, with 5 MW neutral beam input power. In simulations with fully recycling walls and no pumping, an up–down‐symmetric open divertor geometry is compared with the SAS 2 configuration. In density scans without electric or magnetic drifts, the upstream separatrix electron density needed to achieve detachment at both target strike points ( n e, sep, det . ) is ∼35% lower in SAS 2 than in the open configuration, with n e, sep, det . = 1.66 and 2.59 × 10 19 m −3, respectively. With drifts, the same ∼35% difference remains, but detachment density for each configuration is shifted up by ∼15%, giving n e, sep, det . = 1.94 and 2.99 × 10 19 m −3, respectively. Cryopumping is modelled for the SAS 2 divertor, and with a pump duct deep in the upper slot on the common‐flux side, detachment density is shifted up by ∼15–20%. Strong pumping in the upper slot delays detachment there compared with the lower slot, regardless of drift direction. This research sets the stage for future modelling that would explore more sophisticated cryopumping configurations, and sensitivity of divertor performance to changes in magnetic balance and input power.